BALIKPAPAN MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) AND ARTIFICIAL INTELLIGENCE ADOPTION: TOE FRAMEWORK - Jun Prasetyo, Ridho; Andrilla, Riska (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2025)
This study examines the adoption of Artificial Intelligence (AI) among Micro, Small, and Medium Enterprises (MSMEs) in Balikpapan, Indonesia, using the Technology-Organization-Environment (TOE) framework. Through qualitative interviews with seven MSME owners and employees, we explored their perspectives on AI, current technology use, challenges in digital adoption, and external support needs. Findings indicate that while MSME owners recognize the potential of AI to enhance competitiveness, its adoption remains limited, with most relying on basic digital tools like POS systems and social media for marketing. Key challenges include financial constraints, limited digital literacy among staff, and a lack of technical training. Moreover, external support, such as government-backed training programs and financial incentives, is minimal, slowing the digital transition process. This study suggests that expanding AI awareness and providing targeted training could address these barriers, while government policies that promote digital infrastructure and collaboration with tech providers could further support MSME digital transformation. Future research should consider broader variables within the TOE framework, such as cultural and policy-related factors, to provide a more comprehensive understanding of AI adoption in MSMEs across various sectors.